2016
DOI: 10.1089/jwh.2015.5697
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Disease Risk Among Young Urban Women

Abstract: Background: Although young women are presumed to have low cardiovascular disease (CVD) risk and mortality, the mortality benefits secondary to ischemic heart disease have plateaued among young women, <50 years. Materials and Methods: Women, 18-49 years (n = 595) among all participants (n = 1,045) in the Columbia University Heart Health in Action Study, were assessed for CVD risk burden, that is, presence of hypertension, diabetes mellitus, current tobacco use, hyperlipidemia, physical inactivity, and/or obesit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
3
2
0
Order By: Relevance
“…The increased STEMI hospitalization in women aged 18 to 34 and 35 to 44 years are likely multifactorial. 22 , 23 , 24 , 25 , 26 , 27 First, as demonstrated in our study and several other studies, the prevalence of traditional CVD risk factors in women of these age subgroups is increasing at alarming rates. 22 , 23 , 24 , 25 , 26 Also, these risk factors are less likely to be recognized and controlled when compared with the older subgroup (ages 45–55 years).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The increased STEMI hospitalization in women aged 18 to 34 and 35 to 44 years are likely multifactorial. 22 , 23 , 24 , 25 , 26 , 27 First, as demonstrated in our study and several other studies, the prevalence of traditional CVD risk factors in women of these age subgroups is increasing at alarming rates. 22 , 23 , 24 , 25 , 26 Also, these risk factors are less likely to be recognized and controlled when compared with the older subgroup (ages 45–55 years).…”
Section: Discussionsupporting
confidence: 79%
“… 22 , 23 , 24 , 25 , 26 , 27 First, as demonstrated in our study and several other studies, the prevalence of traditional CVD risk factors in women of these age subgroups is increasing at alarming rates. 22 , 23 , 24 , 25 , 26 Also, these risk factors are less likely to be recognized and controlled when compared with the older subgroup (ages 45–55 years). 25 , 26 , 28 Second, the youngest women (18–34 years) were more likely to have nontraditional female‐specific or female‐predominant CVD risk factors such as major depression, autoimmune rheumatological diseases, and history of adverse pregnancy outcomes, with increasing trends over the years.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In addition, there is the fact that this transition may occur in a different manner at each location in middle-income countries, as observed in the present study in which the transition was faster and the association between income and worse cardiovascular risk was inverted only among women 9,23 . An Indian study on a population of an age similar to that of the present one detected a worsening of risk factors among their high-income subjects 9 , whereas a study conducted in the United States on a Hispanic population revealed that, despite the older age of the sample, high-income was associated with a reduction of risk factors 24 . The same has been found among elderly residents in São Paulo, Brazil, where low-income groups had higher CVD risk 25 .…”
Section: Discussionsupporting
confidence: 50%
“…The World Health Organization suggests decreasing the mortality rate of RHD by 25% by the year 2025. "Therefore; an understanding of existing features of the disease in patients living in endemic regions is mandatory" [5].…”
Section: Introductionmentioning
confidence: 99%